Technical and Operational Innovations approaches to firm performance of SMEs auto services sector - KanKam-Kwarteng, Collins; Gatsi, John Gartchie; Acheampong, Stephen; Donkor, Jacob (Archives of Business Research, 2018)
Abstract The purpose of this paper is to provide a framework to help SMEs auto service providers appreciate the critical contribution of innovations (technical and operational) to their performance. Specifically, the study examines the direct relationship between technical innovation and firm performance and the mediating role of operational innovation in the relationship. Participants of the study were drawn from the SMEs auto service provider in Kumasi, Ghana. Multiple regression analysis was performed to estimate the direct relationship and the mediating effects. In all, 180 questionnaires were used for the analysis after performing data screening. The results demonstrate that there is a statistically significant relationship between technical innovation and firm performance. Operational innovation was also found to mediate the relationship between technical innovation and firm performance. The study assumed that information regarding the operations of the participants is complete and that participants were selected based on willingness to participate. It is recommended for future researchers to explore other avenues of the subject matter to develop a standardised pattern of operations in the SMEs auto service sector.